Electronic commerce 2008 : a managerial perspective - Turban, Efraim (Prentice Hall, 2007)
Describing what electronic commerce is, how it is being conducted and managed, and what the major opportunities, limitations, issues and risks are, this book should be of interest to managers and professionals in the business world.